Adult stem cells and regenerative medicine—a symposium report. Issue 1 (26th October 2019) - Cable, Jennifer; Fuchs, Elaine; Weissman, Irving; Jasper, Heinrich; Glass, David; Rando, Thomas A.; Blau, Helen; Debnath, Shawon; Oliva, Anthony; Park, Sangbum; Passegué, Emmanuelle; Kim, Carla; et al.
Abstract: Adult stem cells are rare, undifferentiated cells found in all tissues of the body. Although normally kept in a quiescent, nondividing state, these cells can proliferate and differentiate to replace naturally dying cells within their tissue and to repair its wounds in response to injury. Due to their proliferative nature and ability to regenerate tissue, adult stem cells have the potential to treat a variety of degenerative diseases as well as aging. In addition, since stem cells are often thought to be the source of malignant tumors, understanding the mechanisms that keep their proliferative abilities in check can pave the way for new cancer therapies. While adult stem cells have had limited practical and clinical applications to date, several clinical trials of stem cell–based therapies are underway. This report details recent research presented at the New York Academy of Sciences on March 14, 2019 on understanding the factors that regulate stem cell activity and differentiation, with the hope of translating these findings into the clinic.